2020
DOI: 10.3389/frobt.2020.00007
|View full text |Cite
|
Sign up to set email alerts
|

Altering One's Body-Perception Through E-Textiles and Haptic Metaphors

Abstract: Technologies change rapidly our perception of reality, moving from augmented to virtual to magical. While e-textiles are a key component in exergame or space suits, the transformative potential of the internal side of garments to create embodied experiences still remains largely unexplored. This paper is the result from an art-science collaborative project that combines recent neuroscience findings, body-centered design principles and 2D vibrotactile array-based fabrics to alter one's body perception. We descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…That is, with the chosen sounds we aim not only to resemble feelings in a tactile way (e.g., soft, smooth), but also feelings that could be associated with multisensory real-life experiences, in order to enable different body sensations (e.g., heavy, big, natural). This is in line with prior work suggesting that people can associate haptic patterns (e.g., rocks, clouds) and sounds (e.g., hitting marble) with different body sensations (e.g., being stronger, being lighter, having dryer skin) [17], [34], [44].…”
Section: User Study -Effect Of Sonification On Texture Judgments Body...supporting
confidence: 91%
See 2 more Smart Citations
“…That is, with the chosen sounds we aim not only to resemble feelings in a tactile way (e.g., soft, smooth), but also feelings that could be associated with multisensory real-life experiences, in order to enable different body sensations (e.g., heavy, big, natural). This is in line with prior work suggesting that people can associate haptic patterns (e.g., rocks, clouds) and sounds (e.g., hitting marble) with different body sensations (e.g., being stronger, being lighter, having dryer skin) [17], [34], [44].…”
Section: User Study -Effect Of Sonification On Texture Judgments Body...supporting
confidence: 91%
“…Research question 2 (RQ2): Does the sonification of texture exploration influence participants' subjective sensations of their own hand? Following the work by Tajadura et al, on altering one's body-perception using haptic metaphors [44], we assessed 13 body sensations -speed, weight, strength, naturality, flexibility, hardness, sensitivity, size, tension, viscosity, temperature, moisture, and roughness. In other words, we explored whether some of the perceived haptic attributes of the texture are transferred to participants' hand perception.…”
Section: User Study -Effect Of Sonification On Texture Judgments Body...mentioning
confidence: 99%
See 1 more Smart Citation
“…The visitors were able to try all three vibration patterns with two different surface materials. Results indicated that the different combinations of vibration patterns and surface materials could influence emotional arousal, and bodily sensations related to weight, hardness, strength and size, as described in (Tajadura- Jiménez et al, 2020). The feedback from these try-outs alongside our own bodily experiences informed our decisions about the final prototype.…”
Section: Process: Developing Magic Liningmentioning
confidence: 81%
“… Examples of outcome augmentation technology: Retargeting techniques modulating (A) object quantity ( Azmandian et al, 2016 ), (B,C) object weight ( Rietzler et al, 2018 ; Samad et al, 2019 ), (D) navigation direction ( Sharif et al, 2001 ), (E) navigation elevation ( Nagao et al, 2018 ), and body perception (F,G) ( Tajadura-Jiménez et al, 2019 , 2020 ). Images from the original publications, fully attribution is given to the original authors.…”
Section: Our Approachmentioning
confidence: 99%